DEVELOPMENT OF IDIOPATHIC MACULAR HOLE IN FELLOW EYES: Spectral Domain Optical Coherence Tomography Features. Issue 4 (April 2020) - Choi, Jae Hwan; Kim, Kyung Tae; Kang, Se Woong; Bae, Kunho; Lee, Sang Eon; Kim, Ah Young
Abstract : Purpose: To investigate the long-term incidence and risk factors of macular hole (MH) development in the fellow eyes of patients with unilateral idiopathic MH. Methods: The retrospective case–control study involved the fellow eyes of 215 consecutive patients with idiopathic MH. The patients were classified into two groups according to the presence or development of MH in the fellow eye. The spectral domain optical coherence tomography features and clinical characteristics of each group were compared. Results: Twelve (5.6%) patients presented with bilateral MH at the initial visit, whereas 20 (9.3%) initially unilateral patients developed MH in the fellow eye over a median interval of 44 months. Vitreomacular traction and inner foveal cyst were noted more frequently in the baseline spectral domain optical coherence tomography scans of fellow eyes of the bilateral group ( P < 0.01). An outer foveal defect was found in five patients (35.7%) of the bilateral MH group ( P < 0.01). Conclusion: The incidence of MH in fellow eyes was approximately 10%. The presence of outer foveal defect, inner foveal cyst, and vitreomacular adhesion or traction on spectral domain optical coherence tomography in the fellow eye was the risk factor for MH. Abstract : About 15% of idiopathic macular hole cases developed macular hole in the fellow eye with a median interval of 44 months. The presence of outer foveal defect and inner foveal cyst may constitute risk factors of macular hole development. The prognosis in the second eye was universally better.